Penetapan Harga Swab Antigen oleh Penyedia Jasa Swab di Area Pelabuhan Gilimanuk - Mutia Rahma Maulida; Dwi Fidhayanti, S.HI., M.H. (Komisi Pengawas Persaingan Usaha, 2022)
This study aims to examine more deeply the pricing carried out by clinic service providers in the Gilimanuk area by using the views of Law No. 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. This research is empirical juridical research and using a sociological juridical approach, the data collected is primary and secondary data with data collection methods through observation, interviews, and documentation studies. This research in data processing and analysis goes through several stages: Editing, Classifying, Analyzing, and Verification. Pricing below the market price that is only done by a certain group of swab service providers causes losses and even the closure of competitor swab clinic businesses, although setting prices is the freedom of each company but according to Article 20 of the Law. No. 5 of 1999, the act of pricing below market prices does not need to be based on an agreement to prove legal or illegal, because the truth can be seen from the economic influence that has been compiled in a rule of reason, it is verified until the determination of prices destroys the market and seeks to eliminate its competitors at below prices in general. Keywords: Pricing, Antimonopoly Law, Antigen Swab.